2021
DOI: 10.1039/d1ra01324f
|View full text |Cite
|
Sign up to set email alerts
|

A fluorine-18 labeled radiotracer for PET imaging of γ-glutamyltranspeptidase in living subjects

Abstract: A radiotracer ([18F]GCPA)2 for sensitively and specifically detecting the expression level of γ-glutamyltranspeptidase in living subjects was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…4d shows that the tumor/muscle uptake ratio in the U87 model was 4.15 AE 0.37 at 10 min post injection and 4.21 AE 0.37 at 60 min, which was approximately 2.5 times that in NCI-H1299 tumor-bearing mice (1.63 AE 0.11 at 10 min and 1.77 AE 0.08 at 60 min post injection). They were also higher than those of [ 18 F]1G (o2 within 60 min) and ([ 18 F]GCPA) 2 (2.56 AE 0.19 at 10 min and 2.15 AE 0.06 at 30 min post injection), 25,26 confirming the more prominent targeting specificity of [ 18 F]JM-10. To further demonstrate the targeting specificity of the tracer [ 18 F]JM-10 for GGT, a blocking experiment was also carried out in the U87 tumor-bearing mice pretreated with a GGT enzyme inhibitor (GGsTop).…”
Section: In Vivo Pet Imagingmentioning
confidence: 65%
See 4 more Smart Citations
“…4d shows that the tumor/muscle uptake ratio in the U87 model was 4.15 AE 0.37 at 10 min post injection and 4.21 AE 0.37 at 60 min, which was approximately 2.5 times that in NCI-H1299 tumor-bearing mice (1.63 AE 0.11 at 10 min and 1.77 AE 0.08 at 60 min post injection). They were also higher than those of [ 18 F]1G (o2 within 60 min) and ([ 18 F]GCPA) 2 (2.56 AE 0.19 at 10 min and 2.15 AE 0.06 at 30 min post injection), 25,26 confirming the more prominent targeting specificity of [ 18 F]JM-10. To further demonstrate the targeting specificity of the tracer [ 18 F]JM-10 for GGT, a blocking experiment was also carried out in the U87 tumor-bearing mice pretreated with a GGT enzyme inhibitor (GGsTop).…”
Section: In Vivo Pet Imagingmentioning
confidence: 65%
“…According to the PET imaging results, the radioactivity of the probe in the abdomen accumulated significantly over time. On the one hand, this may be attributed to the strong lipophilicity of [ 18 F]JM-10, whose log P value is significantly higher than that of the probe ([ 18 F]GCPA) 2 (À1.02 AE 0.04 vs. À1.66 AE 0.02), 26 and previous studies have shown that lipophilicity is positively correlated with liver uptake. 34 On the other hand, since GGT is widely distributed in the liver, kidneys and pancreas, the probes targeting GGT tend to show high uptake in these organs.…”
Section: In Vivo Pet Imagingmentioning
confidence: 94%
See 3 more Smart Citations